Marketing the bard : Shakespeare in performance and print, 1660-1740 - Dugas, Don-John, 1967- (University of Missouri Press, 2006)
"Dugas credits the reemergence of Shakespeare's plays and his rise to fame in the 1700s to economic factors surrounding the theater business including the acquisition and adaptation of Shakespeare's plays by the Tonson publishing firm, which marketed collector's editions of his work, spurring a price war and rousing public interest"--Provided by publisher.